Educating children in poor countries - Hillman, Arye L.; Jenkner, E. (Eva); International Monetary Fund ([Washington, D.C.] : International Monetary Fund, 2004)
The problem in many developing countries is that governments lack either the financial resources or the political will to meet their citizens' educational needs. In response, poor parents in some low income countries have organized and paid for their children's education themselves. It is true that school fees and other user payments are a heavy burden for some parents to bear. But, given the alternative - children receiving no education at all - such payments can represent a temporary, if less than ideal, solution to the problem.--Publisher's description.
Keywords: Education, Elementary -- Developing countries; Education and state -- Developing countries; User charges -- Developing countries; Education -- Developing countries -- Costs; Poor children -- Education -- Finance